SCARB1 rs5888 gene polymorphisms in coronary heart disease: A systematic review and a meta-analysis - Ma, Ruchao; Zhu, Xiaoyun; Yan, Bo (Gene, 2018)
Studies have suggested that high-density lipoprotein (HDL) stimulates scavenger receptor class B type 1 (SR-B1) to promote hepatic uptake of cholesterol. SR-B1 is encoded by scavenger receptor class B member 1 (SCARB1) gene in human. A rare mutation in SCARB1 gene has been associated with coronary heart disease (CHD). A polymorphism rs5888 of SCARB1 gene has been linked to CHD risk in humans. The objective was to investigate the relationship between the SCARB1 gene polymorphism rs5888 and risk of CHD. We searched databases of case-control studies and cohort studies on rs5888 polymorphism of SCARB1 gene and risk of CHD. Two reviewers independently screened literature, extracted data, and estimated potential bias of included studies. The quality of the studies was evaluated by recommendation of Newcastle-Ottawa Scale (NOS). Meta-analysis was performed with Stata 12.0 software. Seven studies including 6360 subjects (cases: 2456, controls: 3904) were included in the final data combination. Meta-analysis showed T allele had a lower risk of CHD as compared to C allele in allele model (T vs. C: OR = 0.87, 95% CI: 0.70 to 1.09, P = 0.229). Moreover, we found that T allele or TT/TC had a lower risk of CHD as compared to C/CC in male in allele model (T vs. C: OR = 0.79, 95% CI: 0.61 to 1.01). However, no significant association was observed in women in all allele models. Our findings suggested that polymorphism rs5888 had negative association with CHD, especially in male. However, the conclusion needs further verification with high quality studies with larger sample size and rigorous designs. •A polymorphism rs5888 of SCARB1 gene has been linked to CHD risk in humans.•Exploring the relationship between rs5888 and coronary heart disease•Rs5888 have negative association with coronary heart disease, especially in male.